S.H.A.R.E. Ad Hoc Workshop - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak, (UNIMAS), 2013)
A Workshop/Meeting conducted by the Institute (ISITI) with all the ASEAN partners under S.H.A.R.E. project.